2021
DOI: 10.1186/s40854-021-00227-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic connectedness between stock markets in the presence of the COVID-19 pandemic: does economic policy uncertainty matter?

Abstract: This study investigates the dynamic connectedness between stock indices and the effect of economic policy uncertainty (EPU) in eight countries where COVID-19 was most widespread (China, Italy, France, Germany, Spain, Russia, the US, and the UK) by implementing the time-varying VAR (TVP-VAR) model for daily data over the period spanning from 01/01/2015 to 05/18/2020. Results showed that stock markets were highly connected during the entire period, but the dynamic spillovers reached unprecedented heights during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 88 publications
(90 reference statements)
14
92
0
2
Order By: Relevance
“…As research in the healthcare perspective is starting to yield significant effects, it is now time to focus our attention on the economy and the significant consequences the pandemic has had in this context. A number of scholars have already studied the impact of the global health crisis on financial markets whose sharp fluctuations during the pandemic have led to confusion and uncertainty among investors [14][15][16]. Results reported by other researchers indicate that the SARS-CoV-19 pandemic has changed consumer behaviors [17].…”
Section: Introductionmentioning
confidence: 99%
“…As research in the healthcare perspective is starting to yield significant effects, it is now time to focus our attention on the economy and the significant consequences the pandemic has had in this context. A number of scholars have already studied the impact of the global health crisis on financial markets whose sharp fluctuations during the pandemic have led to confusion and uncertainty among investors [14][15][16]. Results reported by other researchers indicate that the SARS-CoV-19 pandemic has changed consumer behaviors [17].…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury et al (2021) claimed that European financial markets were the most terrible victim related to others. In the same vein, Youssef et al (2021) noticed that European equity markets, excepting Italy, spread more spillovers to the whole other financial markets than they obtained, mainly through the coronavirus outburst. Szczygielski et al (2021b) showed that pandemic insecurity has affected nearly all territories via smaller returns and heightened market volatility.…”
Section: Literature Reviewmentioning
confidence: 90%
“…In order to analyze the causality between the BET index and the number of new COVID-19 cases, we will estimate in the first instance three vector autoregression (VAR) models, much like those found in Anser et al (2021), Chen et al (2021), Chowdhury et al (2021), and Youssef et al (2021), incorporating the stock market index and each COVID-19 pandemic measure, as described below:…”
Section: Quantitative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since now, the scientific literature has not given significant proves for the real economic effects of the COVID-19 pandemic measures. There are good researches on the financial and stock-exchange markets [1][2][3] as well as on employment and staff changes on the micro-level [4][5][6]. Generally, the researches cover the fast moving sectors that are highly dependent by the COVID-19 restriction measures as: economy lock-down and on-line employment, travel shortage and tourism cut-off, transport routs cut-down and supply chains change, individuals uncertainty and financial market change and etc.…”
Section: State Of Artmentioning
confidence: 99%